Advokasi Masyarakat Agraria di Kampung Adat Segunung Berdasarkan Penelitian Adaptasi Digitalisasi Wisata Pedesaan - Praja Firdaus Nuryananda; Leily Suci Rahmatin; Herlina Suksmawati; Thufailah Nafiisah Bilqis (I-Com: Indonesian Community Journal, 2025)
Kampung Adat Segunung is a rural tourism destination located in Jombang that has attempted to implement tourism digitalization through various initiatives. However, these efforts have yet to meet the expectations of local tourism officers. In response, our team, which is also responsible for community service activities, undertook three strategic steps to enhance the capacity of these managers: (1) providing digital literacy training, particularly in tourism marketing; (2) designing and producing roll-up banners in collaboration with Segunung Traditional Village and a local community support organization, Yayasan Akta Bumi; and (3) developing and simulating a tourism package rooted in local wisdom and organically emerging attractions within the village. These initiatives were carried out using the Participatory Rural Appraisal (PRA) approach while integrating the principles of Integrated Marketing Communication (IMC). Through these three measures, the team aims to strengthen the capacity of tourism managers in Segunung Traditional Village, ensuring that their digitalization efforts yield more effective and sustainable outcomes than previous attempts.